The Humanities from the Perspective of Transhumanism and Posthumanism - MIČUNOVIĆ, Milijana; BOSANČIĆ, Boris (Anafora, 2023)
Transhumanism is an intellectual, cultural, scientific, and artistic movement based on the convergence of science, technology, and economy. It supports the growth and application of new scientific and technological solutions in enhancing physical, mental, and other human abilities. On the other hand, posthumanism is a term (or a school of thought) that mostly refers to the redefining of the concept of human(e) in terms of the onto-epistemological, scientific, and biotechnological progress at the end of the twentieth and the beginning of the twenty-first century. Inevitably overlapping, these two movements or schools of thought imminently influence the evolution of the humanities, which are currently experiencing the so-called silent crisis. This crisis manifests in neglecting not only arts and humanities, but also the process of imagination, creativity, and critical thinking in every scientific area. The future of the humanities from the perspective of transhumanism and its value system implies two possible insights. The first refers to the issue of the humanities’ positioning, that is, their relationship towards natural and technical sciences. The other points out the issue of values and skills that the humanities should promote, especially regarding the challenges of the scientific and technological revolution. From the perspective of the posthumanities comes an idea of a complete reconfiguration of the humanities that would replace man as a central figure of humanities’ research. Thus, if the humanities wish to stay relevant and participated in the latest developments, they must morph into posthumanities, ultra-humanities, and metahumanities. Accordingly, critical posthumanities represent an interdisciplinary field focused on new discourse in the area of nonhuman, transhuman, metahuman, and posthuman, that is, a field focused on different perceptions of the concept of “human,” and thus the perception of the humanities in the posthuman age.